FREE-SPACE PROPAGATION OF TERAHERTZ LASER VORTEX BEAMS - Degtyarev, A.; Dubinin, M.; Maslov, V.; Muntean, K.; Svistunov, O. (Radio physics and radio astronomy (Print), 2024)
Subject and Purpose. Currently, numerous ideas and different methods have been in growth for generating vortex beams — areas of the circular motion of the electromagnetic wave energy flow around the so-called phase singularity points caused by a violation of the wave front topological structure. The purpose of this work is to obtain analytical expressions describing the nonparaxial diffraction of wave modes of the waveguide resonator of a terahertz laser during the wave mode interaction with a spiral phase plate. The resulting vortex beams are examined for their physical features in free space propagation. Methods and Methodology. The Rayleigh-Sommerfeld vector theory is adopted to consider the propagation of vortex laser beams generated by wave modes of the quasi-optical waveguide cavity when interacting with a spiral phase plate in different diffraction zones. Results. For the first time, analytical expressions have been obtained to describe the nonparaxial diffraction of wave modes of the waveguide resonator of a terahertz laser, when resonator modes interact with a spiral phase plate at different topological charges, n. The physical features of the resulting vortex beams were studied in their free space propagation. It has been shown that a spiral phase plate modifies the structure of the linearly polarized EH₁₁ mode so that the original (n=0) intensity profile with the maximum energy at the center turns at n=1 and 2 into a ring-like donut shape with an energy hole in the center. The azimuthally polarized TE₀₁ mode has originally (n=0) a ring-shaped intensity. At n=1, this configuration changes to have the maximum intensity in the center. At n=2, it becomes annular again. In the process, the spherical phase front of the beam of the linearly polarized EH₁₁ mode becomes spiral and have one singularity point on the axis, whereas the phase structure of the azimuthally polarized TE₀₁ mode gains a region with two phase singularity points off the axis. Conclusions. The results of the study can effectively facilitate information transfer in high-speed THz communication systems. They can provide a real platform to perform tasks related to tomography, exploring properties of materials, detecting astrophysical sources, which makes them very promising in modern technologies.